2013
DOI: 10.1007/s10157-013-0867-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and daily amount of urinary protein predict the clinical remission rate of tonsillectomy plus steroid pulse therapy for IgA nephropathy

Abstract: BackgroundThis retrospective study was designed to estimate the clinical remission (CR) rate of tonsillectomy plus steroid pulse (TSP) therapy in patients with IgA nephropathy.MethodsBased on 292 of 302 patients with IgA nephropathy treated at 11 Japanese hospitals, we constructed heat maps of the CR rate at 1 year after TSP with the estimated glomerular filtration rate (eGFR), grade of hematuria, pathological grade, number of years from diagnosis until TSP, and age at diagnosis on the vertical axis and the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Mild haematuria (1–29 RBCs/high-power field) was the best predictor of renal deterioration in patients with eGFR> 60 mL/min/1.73m 2 , without severe proteinuria (<100 mg/dL), with an OR of 2.3 (95% CI, 1.2–4.3) for renal deterioration at 10-year follow up [ 25 ]. Furthermore, disappearance of both haematuria and proteinuria has been proposed as clinical remission markers on IgAN [ 26 ] and it is commonly used in clinical trials [ 20 , 27 ]. In addition, the most influential renal guidelines advised that IgAN with haematuria and minimal proteinuria may be a progressive disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mild haematuria (1–29 RBCs/high-power field) was the best predictor of renal deterioration in patients with eGFR> 60 mL/min/1.73m 2 , without severe proteinuria (<100 mg/dL), with an OR of 2.3 (95% CI, 1.2–4.3) for renal deterioration at 10-year follow up [ 25 ]. Furthermore, disappearance of both haematuria and proteinuria has been proposed as clinical remission markers on IgAN [ 26 ] and it is commonly used in clinical trials [ 20 , 27 ]. In addition, the most influential renal guidelines advised that IgAN with haematuria and minimal proteinuria may be a progressive disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, mild haematuria was a predictor of renal deterioration in patients with an estimated glomerular filtration rate (eGFR) of >60 mL/min/1.73 m 2 , without proteinuria (<100 mg/dL) [37]. Disappearance of both haematuria and proteinuria were recently proposed as clinical remission markers in this pathology [61], and both have been used as such in recent clinical trials [62,63]. Therefore, although the majority of studies rule out a repercussion of hematuria on the renal outcome of patients with IgAN, the true role of haematuria on renal function outcome in these patients remains uncertain.…”
Section: Iga Nephropathymentioning
confidence: 96%
“…Although tonsillectomy has been advocated for the treatment of IgAN, most available data on the efficacy of tonsillectomy or TMP have predominantly been from adults . Many studies on tonsillectomy have also been carried out in conjunction with immunosuppressive medication . Hotta et al .…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14]22 Many studies on tonsillectomy have also been carried out in conjunction with immunosuppressive medication. [23][24][25][26] Hotta et al 11 found that TMP reduced proteinuria and improved renal function in IgAN patients during 5 year follow up, and Komatsu et al 27 found that TMP had a significant impact on the disappearance of both proteinuria and hematuria, when compared with steroid pulse treatment alone. Furthermore, a meta-analysis by Liu et al 17 suggested that tonsillectomy, not only as an adjunct treatment but also independently, has significant benefits in inducing clinical remission and reducing the rates of end-state renal disease in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%